2023
DOI: 10.21203/rs.3.rs-2642165/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tumor growth ameliorates cardiac dysfunction and dampens fibrosis in a mouse model for Duchenne Muscular Dystrophy

Abstract: Heart failure and cancer are known to share common risk factors. Nevertheless, until recently, these two were considered separate diseases. Nevertheless, it appears that heart failure and cancer are more connected than initially anticipated. The interplay between heart failure and cancer represents a double-edged sword. While Cardiac remodeling promotes cancer progression, tumor growth suppresses cardiac hypertrophy and reduces fibrosis deposition. Whether these two opposing interactions are connected is curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
1
0
0
Order By: Relevance
“…This is further supported by our previous study in which we implanted cancer cells 10-and 45-days following TAC and subsequently observed the beneficial cardiac effects (12). Interestingly, a recent study from our lab, using MDX mice, an experimental mouse model for Duchenne Muscular Dystrophy (DMD) disorder, revealed that tumor growth inhibits de novo synthesis as well as dissolving existing fibrosis (28). The ability to dissolve existing fibrosis is clearly an important line of research, since it is considered a direly unmet clinical need (29).…”
Section: Discussionsupporting
confidence: 69%
“…This is further supported by our previous study in which we implanted cancer cells 10-and 45-days following TAC and subsequently observed the beneficial cardiac effects (12). Interestingly, a recent study from our lab, using MDX mice, an experimental mouse model for Duchenne Muscular Dystrophy (DMD) disorder, revealed that tumor growth inhibits de novo synthesis as well as dissolving existing fibrosis (28). The ability to dissolve existing fibrosis is clearly an important line of research, since it is considered a direly unmet clinical need (29).…”
Section: Discussionsupporting
confidence: 69%
“…This is further supported by our previous study in which we implanted cancer cells 10-and 45-days following TAC and subsequently observed the beneficial cardiac effects [12]. Interestingly, a recent study from our lab, using MDX mice, an experimental mouse model for Duchenne muscular dystrophy (DMD) disorder, revealed that tumor growth inhibits de novo synthesis as well as dissolving existing fibrosis [32]. The ability to dissolve existing fibrosis is clearly an important line of research, since it is considered a direly unmet clinical need [33].…”
Section: Discussionsupporting
confidence: 68%